Safety of photorefractive keratectomy after Acanthamoeba keratitis - Elisa Moya Kazmarek; Jade Pinto de Queiroz Guerra; Paula Virginia Brom dos Santos Soares; Pablo Felipe Rodrigues; Paula Kataguiri; Bernardo Kaplan Moscovici (Revista Brasileira de Oftalmologia)
ABSTRACT This case report presents a patient who underwent photorefractive keratectomy 13 years after Acanthamoeba infection. The patient experienced prolonged difficulties in epithelialization during the postoperative period, leading to suspicion of reactivation. This case underscores the complexity and challenges in managing patients with a history of photorefractive keratectomy and ocular infections, particularly in cases involving Acanthamoeba. Understanding such cases is crucial for optimizing treatment strategies and achieving favorable outcomes.